Digit ratio (2D:4D) and altruism: evidence from a large, multi-ethnic sample - Galizzi, Matteo M.; Nieboer, Jeroen (Frontiers in Behavioral Neuroscience, 2015)
We look at the links between the Digit Ratio - the ratio of the length of the index finger to the length of the ring finger – for both right and left hands, and giving in a Dictator Game. Unlike previous studies with exclusively Caucasian subjects, we recruited a large, ethnically diverse sample. Our main results are as follows. First, for Caucasian subjects we estimate a significant positive regression coefficient for the right hand digit ratio and a significant negative coefficient for its squared measure. These results replicate the findings of Brañas-Garza et al. (2013), who also observe an inverted U-shaped relationship for Caucasian subjects. Second, we are not able to find any significant association of the right hand digit ratio with giving in the Dictator Game for the other main ethnic groups in our sample. Third, we find no significant association between giving in the Dictator Game and the left hand digit ratio.